The junior encyclopedia of Islam - Khan, Saniyasnain; Erfani, Mohammad Imran (Goodword for Kids Delhi, 2013)
The Junior Encyclopedia of Islam by Saniyasnain Khan introduces young readers to the core beliefs, practices, history, and cultural aspects of Islam in an accessible and engaging way.